"A PLACE SO FAR REMOVED": DYNASTY AND RITUAL IN MONUMENTS FROM CHINKULTIC, CHIAPAS, MEXICO. Issue 2 (2020) - Earley, Caitlin C.
Abstract: The site of Chinkultic in Chiapas, Mexico, remains largely absent from discussions of Classic Maya history and culture, despite a long history of excavation and a substantial corpus of monumental sculpture. This paper explores two groups of sculptures from Chinkultic, photographed using raking-light photographic techniques in 2011 and 2013. Sculptures in the first group depict royal accession and suggest that the rulers of Chinkultic acceded the throne as warriors. The second group of monuments demonstrates a ritual tradition involving rulers and subordinate individuals. Based on analysis of these groups, I argue that Chinkultic was home to consistent artistic programming that performed an elite identity based on warfare and control over surrounding people and places. Combined, these sculptures demonstrate artistic connections between Chinkultic and the Usumacinta region, provide a new window into the sociopolitical history of the Comitán valley, and reflect the innovative artistic programs of frontier places in ancient Mesoamerica.